Effect of particle dispersion on the mechanical behavior of Al-based metal matrix composites reinforced with nanocrystalline Al-Ca intermetallics - Chaubey A.K.; Scudino S.; Mukhopadhyay N.K.; Khoshkhoo M.S.; Mishra B.K.; Eckert J. (My University, 2025)
Al-based metal matrix composites reinforced 20 and 40 vol.% of Al-Ca intermetallic particles have been produced by powder metallurgy. Two distinct approaches have been used for the dispersion of the reinforcing particles within the Al matrix: manual blending and ball milling. Manual blending leads to the agglomeration of the Al-Ca particles to form a cell network throughout the consolidated sample. On the other hand, the composites prepared by milling display a more homogeneous distribution of the reinforcing particles. This has a strong impact on the mechanical properties. The strength increases from 112 MPa for pure Al to 140 and 165 MPa for the blended composites with 20 and 40 vol.%, while the strength increases to 250 and 280 for the corresponding composites produced by milling. This behavior is linked to the reduced matrix ligament size characterizing the milled composites. © 2011 Elsevier B.V. All rights reserved.